2005
DOI: 10.1038/sj.pcan.4500787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ease of using doxazosin in BPH patients with and without hypertension

Abstract: Clinical studies have demonstrated that doxazosin therapy reduced blood pressure (BP) in patients with benign prostatic hyperplasia (BPH) who were hypertensive at baseline but not in patients who were physiologically or pharmacologically normotensive at baseline. In patients with BPH and uncontrolled hypertension, despite treatment with other antihypertensive drugs, the addition of doxazosin resulted in improved control with significant reductions in BP. The new formulation, doxazosin gastrointestinal therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Doxazosin is a safe and efficacious treatment option for lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH), [1][2][3] and as an add-on drug in combination therapy to achieve target blood pressures. [4][5][6][7] Doxazosin contains a chiral carbon at the 2-position of the 1, 4-benzodioxan-2-ylcarbonyl ring, consisting of two optical isomers, (+)-(S)-doxazosin and (-)-(R)-doxazosin, and it is used clinically as a racemate. The (+)-(S)-doxazosin and (-)-(R)-doxazosin do not have the same biological activity.…”
Section: Abstract: Pharmacokinetics;mentioning
confidence: 99%
“…Doxazosin is a safe and efficacious treatment option for lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH), [1][2][3] and as an add-on drug in combination therapy to achieve target blood pressures. [4][5][6][7] Doxazosin contains a chiral carbon at the 2-position of the 1, 4-benzodioxan-2-ylcarbonyl ring, consisting of two optical isomers, (+)-(S)-doxazosin and (-)-(R)-doxazosin, and it is used clinically as a racemate. The (+)-(S)-doxazosin and (-)-(R)-doxazosin do not have the same biological activity.…”
Section: Abstract: Pharmacokinetics;mentioning
confidence: 99%
“…In preliminary experiments, we have further observed that (±)doxazosin obviously enhances the contractile response to 5-HT in isolated longitudinal muscle strips of the rabbit gastric body. Because doxazosin, alfuzosin, and terazosin are orally administered for the treatment of LUTS/BPH or uncontrolled hypertension (Chung et al 1999;Andersen et al 2000;Steers and Kirby 2005;De Alvaro et al 2006;Fine and Ginsberg 2008;Zhang et al 2011), patients can maintain a higher concentration of these agents in the GI tract before drug absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, α 1 -AR antagonists have attracted much attention for the treatment of benign prostatic hyperplasia-related lower urinary tract symptoms, sexual dysfunctions, hypertension, and cardiovascular diseases, while α 2 -AR antagonists have been studied for their activity in a variety of diseases such as pain, depression, anxiety, and obesity …”
Section: Introductionmentioning
confidence: 99%
“…Recently, R 1 -AR antagonists have attracted much attention for the treatment of benign prostatic hyperplasia-related lower urinary tract symptoms, 9 sexual dysfunctions, 10 hypertension, and cardiovascular diseases, 11 while R 2 -AR antagonists have been studied for their activity in a variety of diseases such as pain, 12 depression, 13 anxiety, 14 and obesity. 15 The discovery of a lead candidate or a hit molecule worthy of further development includes characterization of both the affinity/activity and selectivity profiles toward such targets.…”
Section: Introductionmentioning
confidence: 99%